2015
DOI: 10.1016/j.crvi.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic data on the threatened leafcutter ant Atta robusta Borgmeier, 1939 (Formicidae: Myrmicinae: Attini)

Abstract: The karyotype of the threatened ant species Atta robusta is described so as to establish the evolutionary relationships of this taxon with other leafcutter ants. Standard Giemsa staining, C-banding, NOR banding, fluorochromes CMA3/DAPI, Hsc-FA technique and Fluorescence in situ Hybridization (FISH) using 18S rDNA probe were conducted on a population from Aracruz, state of Espírito Santo, Brazil, allowing for comparisons with data available on Atta and other fungus-growing ant species. The diploid chromosome nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 29 publications
(45 reference statements)
2
30
0
2
Order By: Relevance
“…In these species, 2n = 22 and a karyotypic formula of 2n = 18m+2sm+2st were found. Similar banding patterns were also observed in different species (Barros et al 2014a, Murakami et al 1998, Barros et al 2015) which belonged to the three of four species groups defined on the basis of molecular data (Bacci et al 2009). Cytogenetic data on Acromyrmex are also restricted but available for some taxa collected in Brazil: Acromyrmex (Acromyrmex) crassispinus (Forel, 1909); Acromyrmex (Acromyrmex) subterraneus molestans Santschi, 1925; Acromyrmex (Acromyrmex) subterraneus subterraneus Forel, 1893 (Fadini and Pompolo 1996); and in Uruguay: Acromyrmex (Acromyrmex) ambiguus Emery, 1888; Acromyrmex (Acromyrmex) hispidus Santschi, 1925; and Acromyrmex (Moellerius) heyeri (Forel, 1899) (Goñi et al 1983).…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…In these species, 2n = 22 and a karyotypic formula of 2n = 18m+2sm+2st were found. Similar banding patterns were also observed in different species (Barros et al 2014a, Murakami et al 1998, Barros et al 2015) which belonged to the three of four species groups defined on the basis of molecular data (Bacci et al 2009). Cytogenetic data on Acromyrmex are also restricted but available for some taxa collected in Brazil: Acromyrmex (Acromyrmex) crassispinus (Forel, 1909); Acromyrmex (Acromyrmex) subterraneus molestans Santschi, 1925; Acromyrmex (Acromyrmex) subterraneus subterraneus Forel, 1893 (Fadini and Pompolo 1996); and in Uruguay: Acromyrmex (Acromyrmex) ambiguus Emery, 1888; Acromyrmex (Acromyrmex) hispidus Santschi, 1925; and Acromyrmex (Moellerius) heyeri (Forel, 1899) (Goñi et al 1983).…”
Section: Introductionsupporting
confidence: 69%
“…All the species had the same chromosome number, 2n = 38. However, Acromyrmex (Moellerius) striatus (Roger, 1863) has recently shown 2n = 22, with a karyotypic formula of 2n = 20m+2sm (Cristiano et al 2013), the same chromosome number found in all Atta species studied to date (Barros et al 2014a, Fadini and Pompolo 1996, Murakami et al 1998, Barros et al 2015). Since Acromyrmex striatus belongs to the well-supported clade which is quite distinct from other members of the genus Acromyrmex , it is suggested that this species is a sister group of all other leafcutter ants, which split before the divergence between Acromyrmex and Atta (Cristiano et al 2013).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations